2018
DOI: 10.1113/jp275303
|View full text |Cite
|
Sign up to set email alerts
|

HCN4 pacemaker channels attenuate the parasympathetic response and stabilize the spontaneous firing of the sinoatrial node

Abstract: Key points The contribution of HCN4 pacemaker channels in the autonomic regulation of the sino‐atrial node (SAN) has been a matter of debate.The transgenic overexpression of HCN4 did not induce tachycardia, but reduced heart rate variability, while the conditional knockdown of HCN4 gave rise to sinus arrhythmia.The response of the SAN to β‐adrenergic stimulation was not affected by overexpression or knockdown of HCN4 channels.When HCN4 channels were knocked down, the parasympathetic response examined by cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…These results can all be explained by the funny channel counteracting the effectiveness of vagal activity without invoking an intrinsic dependency of HRV on heart period. Kozasa et al (2018) also provide direct support for the relative angle scenario of Figure 5b. In isolated pacemaker cells, the basal diastolic depolarization rate in HCN4 knockdown mice was much slower than in the wild type animals (Kozasa et al, 2018, their figure D, p. 821).…”
Section: Of Hrv Independent Of Vagal Activit Y?supporting
confidence: 59%
See 2 more Smart Citations
“…These results can all be explained by the funny channel counteracting the effectiveness of vagal activity without invoking an intrinsic dependency of HRV on heart period. Kozasa et al (2018) also provide direct support for the relative angle scenario of Figure 5b. In isolated pacemaker cells, the basal diastolic depolarization rate in HCN4 knockdown mice was much slower than in the wild type animals (Kozasa et al, 2018, their figure D, p. 821).…”
Section: Of Hrv Independent Of Vagal Activit Y?supporting
confidence: 59%
“…This appears at first sight to be most compatible with the fixed angle scenario of Figure 5b. However, using a murine genetic knockdown of HCN4, Kozasa et al (2018) reported findings that were at odds with a fixed angle scenario. HCN4 is a main component of the funny channel, and this knockdown model mimics the bradycardic effects of ivabradine, as well as its positive, increasing effects on HRV.…”
Section: Of Hrv Independent Of Vagal Activit Y?mentioning
confidence: 99%
See 1 more Smart Citation
“…Also importantly, GIRK4 channel inactivation has been shown to rescue bradyarrhythmias of HCN4-deficient mice (Mesirca et al, 2014), highlighting a previously unsuspected role of I KACh in counterbalancing I f changes. Complexities in the autonomic modulation of rate have also been described by use of genetically modified mice (Kozasa et al, 2018). These studies suggest that funny channels act to limit excessive bradycardia caused by potent parasympathetic activity.…”
Section: A New Contender: the Ca Clockmentioning
confidence: 88%
“…While non-neural mechanisms of bradycardia, such as HCN4 down-regulation or the HCN4 c.1737+1G>T mutation, presumably express themselves in HRV boost, a drug-induced parasympathetic dominance has shown to lead to a saturation effect of HRV metrics (de Geus, Gianaros, Brindle, Jennings, & Berntson;Goldberger, Challapalli, Tung, Parker, & Kadish, 2001;Kozasa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%